Modelling the Growth of DG Market and the Impact of Incentives on its Deployment: Comparing Fixed Adoption and System Dynamics Methods in Brazil - João Tomé Saraiva (2019)
One of the greatest challenges of power system planners is to incorporate the expected growth of Distributed Generation (DG) in operation and expansion studies, while modeling and understanding its impacts. This paper describes and compares the outcomes of two different methodologies to model the impact of the growth of DG using concepts of the Bass theory of diffusion. We are applying both Fixed Adoption and System Dynamics models using public data and the tariff scenarios proposed in a public consultation developed by the Brazilian Electricity Regulation Agency. The results indicate that the System Dynamics approach can be more suitable to conduct this analysis, since it does not have discontinuities. Additionally, the model and numerical results that are obtained can be used to help the regulatory agency to better design tariff schemes in the public consultation process. (c) 2019 IEEE.